2019
DOI: 10.1002/cben.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Targeted Improvement of Anodic Electron Transfer in Microbial Fuel Cells

Abstract: The concept of the microbial fuel cell (MFC) has existed for over 100 years, but only within the last decade, the practical implementation has become conceivable due to microbial and technical progress. This review article presents available strategies to increase the limiting extracellular electron transfer (EET) in the anode space of MFCs. Therefore, organism‐based improvements as well as the effects of (bio–)polymers and redox mediators on ETT will be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 134 publications
(170 reference statements)
0
10
0
Order By: Relevance
“…3) indicated that ANME seemed to be a weak electricigen in comparison to strong counterparts such as Geobacter [33]. Use of mediators is suggested as an effective method to improve the EET kinetics of weak electricigen [33], which has been intensively confirmed to enhance performance of BESs with different strains as biocatalysts [34,35]. This is proved to be applicable to ANME as well in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…3) indicated that ANME seemed to be a weak electricigen in comparison to strong counterparts such as Geobacter [33]. Use of mediators is suggested as an effective method to improve the EET kinetics of weak electricigen [33], which has been intensively confirmed to enhance performance of BESs with different strains as biocatalysts [34,35]. This is proved to be applicable to ANME as well in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…The overexpression of redox mediators like pyocyanin by P. aeruginosa can enhance the EET in addition to nanowires. P. aeruginosa's biosynthesis pathway was genetically altered, leading to an increase in power density by four times and a 1.6-fold increase in pyocyanin concentration [114]. Additionally, overexpressing NAD synthase in P. aeruginosa increased the quantity of intracellular NAD+/NADH readily available, which boosted the production of pyocyanin by a factor of 1.5 and the power density by a factor of 3 [115].…”
Section: Overexpression Of Electron-conducting Proteinsmentioning
confidence: 99%
“…Conjugated or composite materials have also been shown to improve the performance of microbial electrochemical devices nowadays, which has led to advancement in this field with the aim of designing new materials [132]. Such aims have often been based on composite (metals/oxides/carbon-based) or conjugated (polymers, layer-by-layer structures) materials, mainly to exploit the interactions between carbons, polymers, and the particular organism [133].…”
Section: Metal Oxide and Metal-based Materialsmentioning
confidence: 99%